Apakah perceived usefulness dapat meningkatkan continuance intention? - Larassita, Nilam; Razati, Girang; Sulastri, Sulastri (Business Education Program of Universitas Pendidikan Indonesia, 2019)
The purpose of this study is to find out the perceived usefulness and continuance intention. The design of this study was a cross-sectional method. This study uses a descriptive approach with explanatory survey method. A total of 145 respondents were selected for using probability sampling. A questionnaire was used as a research instrument to collect data from respondents. The analysis technique used is descriptive technique using frequency distribution. Based on the results of the study using descriptive analysis, obtained perceived usefulness results in a good category, and good enough category for continuance intentions. The difference in this study lies in the object of the study, the time of the study, the measuring instrument, the literature used, the theory used and the results of the study.